Modelling and simulation of thin film flow in porous media - Yakubu, Yakubu Salihu (2025)
This thesis explores the behaviour of thin film flow in both porous and non-porous media, considering both single and two-fluid systems. It establishes a comprehensive mathematical framework to describe the flow dynamics under different physical conditions, aiming to clarify the transition between these two regimes. In the case of porous media, the flow is described by the Brinkman equation, which incorporates the effects of permeability and viscous shear.